Evaluation of antihyperglycemic activity of Ficus deltoidea jack and elucidation of its antidiabetic mechanisms using in vitro model - Adam, Zainah (2012)
Diabetes mellitus is a metabolic disease characterized by persistent hyperglycemia. It is the first leading causes of death in developed country and has been an epidemic in many developing countries including Malaysia. This disease remains as a major global health problems even though many antidiabetic drugs are available. This could possibly be due to the limitations of these drugs such as adverse effects and poor clinical efficacy. Therefore, searching for new antidiabetic drugs should be continued. Ficus deltoidea or locally known as Mas cotek is one of the common medicinal plant used in Malaysia. It has been traditionally claimed to possess antidiabetic activity. However, the scientific studies to confirm its efficacy and its possible mode of actions are still lacking. This study was carried out to authenticate the antidiabetic property of F. deltoidea through in vivo antihyperglycemic evaluation and to elucidate its possible antihyperglycemic mechanisms using in vitro model. In vivo antihyperglycemic evaluation was performed in adult male Sprague Dawley rats. Two modes of treatment were applied; acute and sub-chronic. Antihyperglycemic evaluation following acute treatment was carried out in normal and streptozotocin-induced diabetic rats at three different prandial states; fasting, postprandial and post-glucose loaded state. Antihyperglycemic evaluation following sub-chronic treatment (15-days) was carried out in streptozotocin-induced diabetic rats. In vitro antihyperglycemic mechanisms evaluation of F. deltoidea was carried out to elucidate the potential of the plant to stimulate insulin secretion from pancreatic β-cells, to enhance glucose uptake by adipocytes, muscle and liver cells, to augment adiponectin secretion from adipocytes cells and to delay glucose absorption from small intestine by inhibiting α-glucosidase (sucrase) activity. The viability of cells that were used in the in vitro evaluation of antihyperglycemic mechanisms in the presence of F. deltoidea extracts was determined using MTT assay. The results had shown that acute treatment of hot aqueous and ethanolic extracts of F.deltoidea reduced fasting and postprandial hyperglycemia and improved glucose tolerance activity in normal and streptozotocin-induced diabetic rats. Furthermore, following 15-days treatment, hot aqueous extract reduced fasting hyperglycemia and stimulated insulin secretion in streptozotocin-induced diabetic rats. Both extracts did not reduced blood glucose level below the normal range. Antihyperglycemic mechanisms elucidation had revealed that hot aqueous, ethanolic and methanolic extracts of F. deltoidea have significantly stimulated insulin secretion from pancreatic β-cells. Among all extracts, the hot aqueous stimulated the insulin secretion the most and was further evaluated for determination of insulin secreting mechanisms. The result revealed that the insulin secretory action of hot aqueous extract involved K+ ATP channeldependent and K+ ATP- channel independent pathway. The extract also has the ability to induce the uses of intracellular Ca2+ to trigger insulin release. Hot aqueous, ethanolic and methanolic extracts of F. deltoidea significantly enhanced basal and insulin-mediated glucose uptake into adipocytes, muscles and liver cells. The extracts showed either insulin-mimetic or insulin-sensitizing activity or combination of both activities during enhancing glucose uptake into these cells. The ethanolic extract exhibited the highest potential of glucose uptake activity followed by methanolic and hot aqueous extract. Evaluation for adiponectin secretion activity found that the hot aqueous and methanolic extracts of F. deltoidea significantly augmented basal and insulin-mediated adiponectin secretion from adipocytes cells. Hot aqueous extract exhibited higher adiponectin secreting activity as compared to methanolic extract. Meanwhile, ethanolic extract did not showed any effect on adiponectin secretion activity. α-Glucosidase inhibition study showed that hot aqueous, ethanolic and methanolic extracts of F. deltoidea significantly inhibited in vitro and in vivo rat intestine α-glucosidase (sucrase) activity. All extract possess mixed-type inhibition mechanism against this enzyme activity. The in vivo study had shown that these extracts ameliorate postprandial hyperglycemia following sucrose administration in normal and diabetic rats. Among all extracts, methanolic possesses the most potent rat intestine sucrase inhibitory activity. The viability study showed that methanolic extract at higher concentrations (500 and 1000 μg/ml) exhibited cytotoxic effect against BRIN BD11 cells and ethanolic at the same concentration possess cytotoxic effect against BRIN BD11 and L6 myotubes. Therefore, insulin secreting and glucose uptake activities possess by both extracts could not be taken into consideration. In conclusion, this study had shown that F. deltoidea has the ability to reduce hyperglycemia following acute and sub-chronic treatment. The suggested mechanisms by which F. deltoidea reduce hyperglycemia are stimulation of insulin secretion from pancreatic β-cells, enhancement of glucose uptake into adipocytes, muscle and liver cells,augmentation of adiponectin secretion from adipocytes cell and inhibition of α-glucosidase activity in small intestine. This dual pancreatic and extrapancreatic action of F. deltoidea together with its ability to maintain normal glycemia illustrate the enormous potential of this plant to be developed as new oral antidiabetic agent. Furthermore, adiponectin secreting and insulin-sensitizing activities exhibited by F.deltoidea indicated that this plant has the ability to ameliorate insulin resistance and may potentially be beneficial for the treatment of insulin-resistance related-Type 2 diabetes mellitus.